The effect of artificial reef configuration on wave breaking intensity relating to recreational surfing conditions - Johnson, Craig Michael (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScEng (Civil Engineering))--University of Stellenbosch, 2009.